Optoelectronics Using 2D Colloidal Nanocrystals from Wide Band Gap to Narrow Band Gap Materials. Issue 10 (4th September 2017) - Martinez, Bertille; Livache, Clément; Goubet, Nicolas; Izquierdo, Eva; Silly, Mathieu G.; Ithurria, Sandrine; Lhuillier, Emmanuel
Abstract : Colloidal nanocrystals are playing an increasing role for the development of low cost optoelectronics. Among these materials, 2D nanoplatelets (NPL) offer particularly well‐controlled optical features and their integration into device such as transistor and photoconductor is here discussed. We present recent results obtained on the optoelectronic properties of CdSe/CdS and HgTe 2D nanoplatelets (NPL). The manuscript is organized along three main sections. The first part is an introduction to 2D NPLs and their structural and optical properties. The second part gets focused on CdSe/CdS NPL and their photoconductive properties. We in particular highlight the key role plays by the 2D geometries on the charge dissociation. Finally the last part of the paper discusses about the recent report of HgTe and HgSe NPL with optical features in the near infrared. Here we discuss how the surface chemistry can be used to tune the majority carrier and the photoconductive properties of the material. Abstract : The paper discusses recent results regarding the optoelectronic properties of II–VI semiconductor 2D nanoplatelets. A particular focus is put on the correlation between electronic structure and transport properties.